A method of measuring acoustic absorption coefficient of a material specimen using a dynamic microphone - Xie, Jin. (2013)
This paper reports the development of a method for measuring the absorption coefficient of a material specimen mounted at one end of a planar wave tube using a dynamic microphone at the other end. In the proposed method, the dynamic microphone mounted is used as an actuator (loudspeaker) to generate sound waves and simultaneously performs as a probe to sense acoustic impedance at the same point. For the electro-mechanical acoustical system formed by the dynamic microphone and the tube, a “transduction matrix” is introduced to relate the input electrical variables (voltage and current) and the output acoustical variables (pressure and particle velocity). Once the matrix is calibrated, probing the input voltage and current to the dynamic microphone alone allows quantitative evaluation of the acoustic impedance of material specimen, from which absorption coefficient of the material is calculated. Measurements of fully-reflected end, anechoic end and a porous material specimen are carried out and compared to the results obtained by the conventional transfer function method. It is found that the results match well with each other in a frequency range depending on the length of the tube.